Leptin levels in gingival crevicular fluid in periodontal health, chronic and aggressive periodontitis - Hala Samir Abdalla Eldessouky; Ibtihal Hamdy; Mona Shoeib; Olfat Gameel Shaker (Cairo : Hala Samir Abdalla Eldessouky, 2013)
The aim of the present study was to assess GCF leptin concentrations in healthy, chronic and aggressive periodontitis and to explore leptin levels in both healthy and diseased sites in aggressive periodontitis. A total of thirty subjects were selected based on their body mass index for the study. The subjects were divided into three groups of 10 patients each: Group {u2160}: Healthy periodontium, Group {u2161}: Chronic periodontitis and Group {u2162}: Aggressive periodontitis. GCF samples were collected to estimate leptin levels using enzyme-linked immunosorbent assay kit
Thesis (M.Sc.) - Cairo University - Faculty of Oral and Dental Medicine - Department of Periodontology
Issued also as CD
Keywords: Aggressive periodontitis; Chronic periodontitis; Leptin